Analisis Pola Asuh Orang Tua dalam Penerapan Pendidikan Seks untuk Pencegahan Kekerasan Seksual Sejak Dini di Play Group Eleos Surabaya - Putri, Niken Cahyaning; Yulianingsih, Wiwin (J+PLUS UNESA, 2023)
The purpose of this study is to determine the profile of parenting patterns applied by parents and the application of sex education in early childhood. This research is motivated by the rampant sexual crimes against children and the lack of sex education in schools. One of the factors assumed to be the cause is the lack of information for children related to preventive measures and self-defense that can be provided in sex education. Sex education for children is still considered taboo by the community. The method used in this research is descriptivequalitative, involving eight informants from the families of Play Group Eleos Surabaya students. The results in this study show that all informants have a tendency to apply democratic parenting and have views on the importance of sex education for children, but are still limited to the introduction of sex or gender differences. The recommendations given are that parents should seek accurate and appropriate information about various ways and methods of introducing sex education to their children in accordance with their developmental stages.